Case Report: Contiguous Xq22.3 Deletion Associated with ATS-ID Syndrome: From Genotype to Further Delineation of the Phenotype - Smetana, Jan; Vallova, Vladimira; Wayhelova, Marketa; Hladilkova, Eva; Filkova, Hana; Horinova, Vera; Broz, Petr; Mikulasova, Aneta; Gaillyova, Renata; Kuglík, Petr (Frontiers in Genetics, 2021)
Alport syndrome with intellectual disability (ATS-ID), also known as AMME complex (OMIM #300194), is an X-linked contiguous gene deletion syndrome associated with an Xq22.3 locus mainly characterized by haematuria, renal failure, hearing loss/deafness, ID/mental retardation (MR), midface hypoplasia and elliptocytosis. . It is thought that ATS-ID is caused by the loss of function of COL4A5 (ATS) and FACL4 (=ACSL4) (ID) through the interstitial (micro)deletion of chromosomal band Xq22.3. We report detailed phenotypic description and results from genome-wide screening of Czech family with diagnosis ATS-ID (proband, maternal uncle and two female carriers). Female carriers showed mild clinical features of microscopic haematuria only, while affected males displayed several novel clinical features associated ATS-ID. Utilization of whole- exome sequencing (WES) discovered the presence of approximately 3Mb deletion in Xq23 area, which affected 19 genes from TSC22D3 to CHRDL1. We compared the clinical phenotype with previously reported three ATS-ID families worldwide and correlated their complex clinical manifestations with the extent of the deleted chromosomal region. In addition to previously described phenotypes associated with aberrations in AMMECR1 and FACL4, we identified two genes, member of tripartite motif (TRIM) family MID2 and subunit of the proteasome PA700/19S complex (PSMD10), respectively, as prime candidate genes responsible for additional clinical features observed in our patients with ATS-ID. Overall, our findings further improve the knowledge about clinical impact of Xq23 deletions and bring novel information about phenotype/genotype association of this chromosomal aberration